Association between characteristics of Western blot bands and immune function in patients with HIV-1 infection - Fenfang DONG; Yahui XU; Laizhou WU (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2024)
Objective Through the analyses of the Western blot (WB) band type and CD4+ T lymphocyte (CD4 cells) count in patients with HIV-1 infection to explore the association between the characteristics of WB bands and the immune status of patients with HIV-1 infection, and to provide a basis for clinical diagnosis and treatment. Methods A total of 271 patients with HIV-1 infection were enrolled. The CD4 cell count and WB band type of the venous blood from the infected patients were detected by flow cytometry and immunoblotting, respectively. The relationship between different ages and gender, and the severity of immunodeficiency and WB band type were analyzed. Results The severity of immunodeficiency (χ2=28.65, P<0.001), but not the distribution of WB bands, differed significantly among different age groups. However, the distribution of p55 band (χ2=4.51, P<0.05), but not the severity of immunodeficiency, was significant different between genders. The distribution of the WB band types of p31, p55 and p17 varied greatly with immune status (χ2=7.87, 19.44, 7.95, P<0.05 for all). Similarly, immune status significantly influenced the detection rates of the HIV-1 band, gag gene coding protein band, p55+p31 deficiency, and p55+p17 deficiency (χ2=4.75, 16.23, 8.51, 8.00, P<0.05 for all). Conclusions The immune status of infected individuals can affect the characteristics of WB bands. The simultaneous loss of p17 and p55 bands may be related to the severity of HIV infection. Analyses of WB bands would be helpful for evaluating the efficacy of AIDS treatment and monitoring the immune reconstitution.